2014
DOI: 10.1590/s0100-06832014000500016
|View full text |Cite
|
Sign up to set email alerts
|

Animal manure phosphorus characterization by sequential chemical fractionation, release kinetics and 31P-NMR analysis

Abstract: SUMMARYPhosphate release kinetics from manures are of global interest because sustainable plant nutrition with phosphate will be a major concern in the future. Although information on the bioavailability and chemical composition of P present in manure used as fertilizer are important to understand its dynamics in the soil, such studies are still scarce. Therefore, P extraction was evaluated in this study by sequential chemical fractionation, desorption with anion-cation exchange resin and 31 P nuclear magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…They reported that inorganic P was the most significant form of P both in the compost and compost-amended soils. Another study reported that P forms from poultry, cattle, and swine dry manures are bioavailable and in organic in nature and dependent on Ca:P ratio in manures [34]. Ajiboye et al [35] 30 to 40% of total hog and cattle manure P and 10% of total biosolids P was extracted with water, and 21 to 32% of total P in all organic amendments was extracted with NaHCO 3 except in dairy cattle manure (45% of total P).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that inorganic P was the most significant form of P both in the compost and compost-amended soils. Another study reported that P forms from poultry, cattle, and swine dry manures are bioavailable and in organic in nature and dependent on Ca:P ratio in manures [34]. Ajiboye et al [35] 30 to 40% of total hog and cattle manure P and 10% of total biosolids P was extracted with water, and 21 to 32% of total P in all organic amendments was extracted with NaHCO 3 except in dairy cattle manure (45% of total P).…”
Section: Resultsmentioning
confidence: 99%
“…Highest increases were observed in Av-P and Inorg-P, because between 60 % (Cassol et al, 2001) and 99 % (Tiecher et al, 2014) of P contained in PS is in inorganic forms. This increase was up to 12.5-fold in the Av-P/Total-P ratio in the 0.00-0.05 m soil layer where PS was applied at the maximum rate (Table 4).…”
Section: Discussionmentioning
confidence: 95%
“…The field-applied P contained in PS in Brazil is estimated at around 123 thousand tons per year (Tiecher et al, 2014), representing about 3.2 % of the annual consumption of P contained in phosphate fertilizers in Brazil (3,860 thousand tons per year) (IFA, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also the possibility of the excess supply of P causing environmental contamination leading to the eutrophication of water courses. In this case, greater attention should be paid to P fractions with greater lability and mobility in the soil, such as those associated with water-soluble inorganic phosphates, due to them having the greatest potential for causing environmental contamination (LI et al, 2014;TIECHER et al, 2014;TORRI et al, 2017).…”
Section: Introductionmentioning
confidence: 99%